The relationship between limb length and lower-limb explosive power on squat-style long jump performance in junior secondary students - Octaviani, Karina; Nurrochmah, Siti (CV Rezki Media, 2025)
Background: To determine the relationship between leg length and leg muscle explosive power with squat style long jump performance applied to junior high school students. Objectives: This study examines the relationship between leg length, leg muscle explosive power, and the ability to jump squatting style long. Methods: The method used is a quantitative descriptive design with a correlational study. The study population amounted to 60 male students in class VIII. Sampling using the Purposive Proportional Systematic Random Sampling technique amounted to 45 students. The collected data were analyzed using three prerequisite tests: data normality test, homogeneity test, and linearity test. After fulfilling the prerequisite test requirements, it can be continued with 4 hypothesis tests, product moment test, multiple correlation test, regression equation line, and practical contribution and relative contribution. Results: The data obtained using inferential statistics in multiple correlation analysis is complemented by multiple regression analysis. The results of the multiple correlation test obtained a coefficient = 0.687 and Sig. P = 0.001 < a = 0.05. Conclusions: The study concludes a positive and linear relationship between leg length and leg muscle explosive power with squat-style long jump performance. Based on these findings, further research is recommended to explore additional variables such as speed, flexibility, and confidence, which may influence squat-style long jump performance.